The miRNAs 203a/210‐3p/5001‐5p regulate the androgen/androgen receptor/YAP‐induced migration in prostate cancer cells - Chieh Huo; Ying‐Yu Kuo; Ching‐Yu Lin; Shine‐Gwo Shiah; Chia‐Yang Li; Shu‐Pin Huang; Jen‐Kun Chen; Wen‐Ching Wang; Hsing‐Jien Kung; Chih‐Pin Chuu (Cancer Medicine, 2024)
Abstract Background Prostate cancer (PCa) patients with elevated level of androgen receptor (AR) correlate with higher metastatic incidence. Protein expression of AR and its target gene prostate‐specific antigen (PSA) are elevated in metastatic prostate tumors as compared to organ‐confined tumors. Androgen treatment or elevation of AR promotes metastasis of PCa in cell culture and murine model. However, under androgen depleted condition, AR suppressed cell mobility and invasiveness of PCa cells. Androgen deprivation therapy in PCa patients is associated with higher risk of cancer metastasis. We therefore investigated the dual roles of AR and miRNAs on PCa metastasis. Methods The PC‐3AR (PC‐3 cells re‐expressing AR) and LNCaP cells were used as PCa cell model. Transwell migration and invasion assay, wound‐healing assay, zebrafish xenotransplantation assay, and zebrafish vascular exit assay were used to investigate the role of AR and androgen on PCa metastasis. Micro‐Western Array, co‐immunoprecipitation and Immunofluorescence were applied to dissect the molecular mechanism lying underneath. The miRNA array, miRNA inhibitors or plasmid, and chromatin immunoprecipitation assay were used to study the role of miRNAs on PCa metastasis. Results In the absence of androgen, AR repressed the migration and invasion of PCa cells. When androgen was present, AR stimulated the migration and invasion of PCa cells both in vitro and in zebrafish xenotransplantation model. Androgen increased phospho‐AR Ser81 and yes‐associated protein 1 (YAP), decreased phospho‐YAP Ser217, and altered epithelial‐mesenchymal transition (EMT) proteins in PCa cells. Co‐IP assay demonstrated that androgen augmented the interaction between YAP and AR in nucleus. Knockdown of YAP or treatment with YAP inhibitor abolished the androgen‐induced migration and invasion of PCa cells, while overexpression of YAP showed opposite effects. The miRNA array revealed that androgen decreased hsa‐miR‐5001‐5p but increased hsa‐miR‐203a and hsa‐miR‐210‐3p in PC‐3AR cells but not PC‐3 cells. Treatment with inhibitors targeting hsa‐miR‐203a/hsa‐miR‐210‐3p, or overexpression of hsa‐miR‐5001‐5p decreased YAP expression as well as suppressed the androgen‐induced migration and invasion of PCa cells. Chromatin immunoprecipitation (ChIP) assay demonstrated that AR binds with promoter region of has‐miR‐210‐3p in the presence of androgen. Conclusions Our observations indicated that miRNAs 203a/210‐3p/5001‐5p regulate the androgen/AR/YAP‐induced PCa metastasis.